EFFECT OF TRAYUSHNADI ANJANA IN THE MANAGEMENT OF KAPHAJA ABHISHYANDA W.S.R VERNAL KERATOCONJUNCTIVITIS: A PILOT STUDY - Dubey, *Parinita; Sriyash dubey (International Journal of Ayurveda and Pharma Research, 2019)
Vernal Keratoconjunctivitis is an unusually severe sight threatening allergic eye disease, in which patient suffers from intense itching, photophobia, tearing and heaviness in eyes and so on. It occurs mainly in children of age group between 5 to 20 years mainly and the disease requires long term medications. On reviewing the clinical presentation from all the Ayurvedic texts it is found that Vernal Keratoconjunctivitis ensembles with Kaphaja Netra Abhishyanda. Ayurvedic treatment could bring very promising result in bringing down the signs and symptoms of Vernal Keratoconjunctivitis with the following. Aim and Objective: To evaluate the efficacy of Trayushnadi Anjana in Kaphaja Netra Abhishyanda/ Vernal Keratoconjunctivitis. Material and Methods: 15 clinically diagnosed patients of Kaphaja Netra Abhishyanda/ Vernal Keratoconjunctivitis were randomly selected from OPD/IPD of Rishikul Ayurvedic College and Hospital, Haridwar. Local application of eye-ointment Trayushnadi Anjana on lower fornix was given 2 times a day on each eye, for 15 days. Results: 6.7% patients were cured, 33.3% patients were marked improved 33.3% patients were moderately improved and 26.7% patients were mild improved. Important observation and conclusion: Trayushnadi Anjana showed good results in itching, stickiness, watering and redness in both the eyes of patients who were selected for this study.